Which Coronary Lesions Are More Prone to Cause Acute Myocardial Infarction? - Taner Sen; Mehmet Ali Astarcioglu; Osman Beton; Lale Dinc Asarcikli; Celal Kilit (Arquivos Brasileiros de Cardiologia)
Abstract Background: According to common belief, most myocardial infarctions (MIs) are due to the rupture of nonsevere, vulnerable plaques with < 70% obstruction. Data from recent trials challenge this belief, suggesting that the risk of coronary occlusion is, in fact, much higher after severe stenosis. The aim of this study was to investigate whether or not acute ST-elevation MIs result from high-grade stenoses by evaluating the presence of coronary collateral circulation (CCC). Methods: We retrospectively included 207 consecutive patients who had undergone primary percutaneous coronary intervention for acute ST-elevation MI. Collateral blood flow distal to the culprit lesion was assessed by two investigators using the Rentrop scoring system. Results: Out of the 207 patients included in the study, 153 (73.9%) had coronary collateral vessels (Rentrop 1-3). The Rentrop scores were 0, 1, 2, and 3 in 54 (26.1%), 50 (24.2%), 51 (24.6%), and 52 (25.1%) patients, respectively. Triglycerides, mean platelet volume (MPV), white cell (WBC) count, and neutrophil count were significantly lower in the group with good collateral vessels (p = 0.013, p = 0.002, p = 0.003, and p = 0.021, respectively). Conclusion: More than 70% of the patients with acute MI had CCC with Rentrop scores of 1-3 during primary coronary angiography. This shows that most cases of acute MI in our study originated from underlying high-grade stenoses, challenging the common believe. Higher serum triglycerides levels, greater MPV, and increased WBC and neutrophil counts were independently associated with impaired development of collateral vessels.